Situation Report: Romania, 2 September 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. New Romanian Mediation in Middle East UN Secretary-General Javier Perez de Cuellar Romanian-French Relations Romania's Cultural Patrimony: Propaganda and Practice A Dog's Life in Present-Day Romania More on Corruption in Foreign Trade A Major Increase of Consular Fees